2020
DOI: 10.2147/dmso.s268992
|View full text |Cite
|
Sign up to set email alerts
|

<p>Triglyceride to High-Density Lipoprotein Cholesterol Ratio is an Important Determinant of Cardiovascular Risk and Poor Prognosis in Coronavirus Disease-19: A Retrospective Case Series Study</p>

Abstract: Background Acute myocardial injury and heart failure characterized by elevated cardiac troponin and decreased heart pump function are significant clinical features and prognostic factors of coronavirus disease-19 (COVID-19). Triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio is an indicator of insulin resistance. This study aimed to explore the association of the TG/HDL-C ratio with cardiovascular risk and prognosis in COVID-19. Methods Ninety-eight l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
(13 reference statements)
3
27
1
Order By: Relevance
“…With recovery from COVID-19 infection the lipid levels return towards levels present prior to infection ( 28 , 29 , 30 , 42 , 43 ). As expected, the greater the severity of the illness the greater the reduction in LDL-C and/or HDL-C levels ( 29 , 31 , 32 , 33 , 34 , 35 , 36 , 38 , 42 , 44 , 45 ). LDL-C and HDL-C levels are inversely correlated with C-reactive protein (CRP) levels i.e., the higher the CRP levels the lower the LDL-C or HDL-C level ( 28 , 29 , 31 , 45 ).…”
Section: Effect Of Infections On Lipid and Lipoproteinssupporting
confidence: 70%
See 2 more Smart Citations
“…With recovery from COVID-19 infection the lipid levels return towards levels present prior to infection ( 28 , 29 , 30 , 42 , 43 ). As expected, the greater the severity of the illness the greater the reduction in LDL-C and/or HDL-C levels ( 29 , 31 , 32 , 33 , 34 , 35 , 36 , 38 , 42 , 44 , 45 ). LDL-C and HDL-C levels are inversely correlated with C-reactive protein (CRP) levels i.e., the higher the CRP levels the lower the LDL-C or HDL-C level ( 28 , 29 , 31 , 45 ).…”
Section: Effect Of Infections On Lipid and Lipoproteinssupporting
confidence: 70%
“…As observed with other infections numerous studies have reported a decrease in total cholesterol, LDL-C, and HDL-C levels and variable changes in triglycerides in patients with COVID 19 infections ( 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ). As expected, apolipoprotein A-I and B were also decreased ( 39 , 40 , 41 ).…”
Section: Effect Of Infections On Lipid and Lipoproteinssupporting
confidence: 59%
See 1 more Smart Citation
“…Thirty-two studies were retrospective ( 7 , 21 23 , 27 , 29 , 31 39 , 41 45 , 48 , 50 , 51 , 53 , 55 , 57 63 ), eight prospective ( 24 , 30 , 46 , 47 , 49 , 52 , 54 , 56 ), whereas the remaining four did not report the study design ( 25 , 26 , 28 , 40 ). Clinical endpoints included disease severity based on current clinical guidelines in 15 studies ( 21 , 24 , 33 , 39 41 , 43 , 48 , 54 , 55 , 57 59 , 62 , 63 ), hospitalization in one ( 37 ), ICU transfer in three ( 32 , 44 , 49 ), or need for mechanical ventilation in one ( 23 ), and survival status in 24 studies ( 7 , 22 , 25 31 , 34 36 , 38 , 42 , 45 47 , 50 53 , 56 , 60 , 61 ). Sixteen studies reported plasma BNP concentrations ( 23 , 24 , 26 , 33 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…Retrospective American study analyzed 6,439 patients hospitalized due to COVID-19 presented that patients previously diagnosed with heart failure had poorer outcome, stayed in the hospital longer and had a higher risk of mechanical ventilation and mortality, regardless of left ventricle ejection fraction [16]. Zhang et al confirmed that inappropriate lipid parameters described as increased triglycerides/high-density lipoprotein cholesterol (TG/HDL-C) ratio had been considered as risk factors of myocardial injury, heart failure, COVID-19 severity and fatal outcome [17].…”
Section: Impact Of Chronic Disease On the Sars-cov-2 Infection's Coursementioning
confidence: 99%